Causes and consequences of variation in diet composition of nestling Canada jays. (27th January 2021) - Freeman, Nikole E.; Newman, Amy E. M.; Sutton, Alex O.; Kyser, T. Kurt; Norris, D. Ryan
Abstract : Diet quality during development can impact growth, physiology, behaviour and survival. The Canada jay is a resident boreal passerine that caches a wide variety of perishable food items in late summer and autumn for its over‐winter survival and late‐winter reproduction. A previous experiment found evidence that food supplementation of Canada jay pairs during the nestling period had a positive effect on the condition of their nestlings. However, given that foods cached by adults vary widely in nutritional content, the composition of nestling diets could also have an important influence on offspring development. In a population of Canada jays in Algonquin Provincial Park, Ontario, Canada, we investigated the influence of environmental conditions before and during the breeding season on nestling diet composition and the consequences of nestling diet composition on the body condition of nestlings and on their subsequent survival. Using stable‐carbon (δ 13 C) and ‐nitrogen (δ 15 N) isotopes, we estimated the proportion of three food groups (vertebrates + human food, invertebrates and plants) in feathers from almost 200 nestlings. Nestling diet in March and April was influenced by environmental conditions 5–6 months prior to hatching, with warmer and more variable autumn temperatures associated with a greater proportion of vertebrate flesh and human food in the diet. However, the proportion of vertebrates and human food in the diet had no influence on nestling body condition or whether an individual was observed the following fall. Our results, in conjunction with previous work on Canada jays, suggest that the quantity of food available to a nestling during development may be more important than diet composition.